Classification in hydrologic groups of soil of Uruguay - Durán, A. (Agrociencia Uruguay, 1997)
Dominant soils of the mapping units of the Reconnaissance Soil Map of Uruguay were tentatively classified in hydrologic groups (GH) following the procedure developed by the U.S. Soil Conservation Service (SCS). Since information on the relationship between precipitation and runoff is not available yet, the classification is mostly based on soil morphology: horizons sequence, their texture and structure, soil matrix color, mottling and presence of Fe-Mn concretions as indications of redoximorphic phenomena. Estimates of soil permeability and drainage on the basis of profile morphology and the knowledge of the hydric regime support the classification in GH. The results show that only very few soils are included in Group A, mainly Arenosols (Psamments) or very gravelly soils. Group B (24 profiles) includes mainly moderately well to well drained Subeutric Brunosols (Udolls). Group C (68 profiles) includes Subeutric and Eutric Brunosols (Udolls) and Argisols (Udolls and Udalfs), mostly moderately well to somewhat poorly drained, with a fine textured subsoil. Group D (63 profiles) includes all Vertisols, Planosols (Albolls and Aqualfs), Gleysols (mostly Aquolls and Udolls) and solonetzic soils (Aqualfs), most Litosols (Lithic Orthents and Udolls) and a few Brunosols (Udolls); drainage range from somewhat excessive to poor. the classification achieved is razonably consistent with available information on infiltration rate and hydraulic conductivity measurements for some soils. The comparison with known soils of USA, classified in GH with a more scientific basis, has not shown any evident contradiction between the classification criteria used both in US and Uruguay to assign each soil to the correct GH.